Synthesis and structural studies of lanthanum (III) dialkyldithiocarbamate, 1,10-phenantrolien - Ibrahim Baba; Indah Raya; Bohari Mohd Yamin (Universiti Kebangsaan Malaysia, 2009)
A new series of lanthanum dialkyldithiocarbamate complexes with 1,10-phenantroline were successfully synthesized using in situ methods. These complexes were characterized using elemental analysis, infrared, thermogravimetric analysis and conductivity. Microelemental analysis data were in agreement with the general formula La(S2CNR’R”)3phen (R’=ethyl, methyl; R”=butyl, heptyl, isopropyl, isobutyl, benzyl and cyclohexyl; phen = 1,10-phenantroline). Infrared spectra of complexes showed the thioureide ν(C-N) bands were in the region of 1450 - 1482 cm-1. The single ν(C-S) bands appeared in the region of 959 – 997 cm-1 and ν(C-H) bands in the region of 2918-2955 cm-1. The crystal structure of tris(N,Nethylbenzyldithiocarbamate)( 1,10-phenantroline)lantanum(III) adopts an orthorombic system (space group Pccn) with a distorted dodecahedron geometry with a = 19.865(5) Å , b = 42.803(10) Å, c = 10.657(3) Å, α = β = γ= 90o and Z = 9. Three dithiocarbamates and one phenanthroline ligands were coordinated to the central La atom in bidentate manner.